Synthesis of conjugated polymers with pendant metal complexes and study of their photophysical properties - Tsoi, Ka-wing (The University of Hong Kong (Pokfulam, Hong Kong), 2015)
A series of copolymers based on poly(phenylene thienylene) mainchain that contains pendent bisterpyridine ruthenium(II) complexes was synthesized by palladium catalyzed Suzuki coupling reaction. The polymers contain different proportion of metal complexes. The copolymers exhibit broad absorption band in the visible region due to the conjugated backbone and the bisterpyridine ruthenium complexes. The relative intensity of each absorption band depends on the metal complex contents. There is a significant spectral overlap between the emission of the conjugated polymer mainchain and the absorption of the ruthenium complexes. It was found that there is a quenching of polymer emission by the complexes. Based on the results obtained by spectroscopic studies, it is proposed to be Förster type energy transfer process between the polymer mainchain as the donor and the complexes as the acceptors.